Neutron diffraction study of the magnetic structures of manganese succinate Mn(C4H4O4): A complex inorganic-organic framework - Saines, P; Hester, JR; Cheetham, A (2010)
The antiferromagnetic structures of the Mn succinate framework, Mn(C 4H4O4), have been determined using neutron diffraction. The structure comprises alternating layers containing chains of edge-sharing Mn (II) O6 octahedra and sheets of corner-sharing Mn (II) O6 octahedra, respectively, with a layer separation of ∼7.5. At 10 K the edge-sharing MnO6 octahedral chains order antiferromagnetically into a collinear sinusoidal spin structure with a propagation vector k2 = (0,-0.5225,0), in which individual edge-sharing MnO6 chains are ferromagnetically ordered. The sheets of corner-sharing MnO6 octahedra order magnetically at 6 K, adopting the antiferromagnetic structure expected for a square arrangement of cations with a propagation vector k8 = (-1,0,1). The ordering of these sheets at a lower temperature than the chains is consistent with their longer nearest-neighbor superexchange pathway. The magnetic structure of the edge-sharing layers is unaffected by the 6 K phase transition, indicating that the orderings of the two different layers are essentially independent of each other. © 2010 The American Physical Society.